2031. False-positive Serologic Results attributable to IVIG therapy. (26th November 2018) - Hanson, Kimberly E; Gabriel, Nielsen; Mchardy, Ian; Hoffmann, Wesley; Cohen, Stuart H; Welch, Ryan; Couturier, Marc Roger; Thompson, George R
Abstract: Background: Intravenous immunoglobulin (IVIG) is used to treat an increasing number of conditions including hematologic, rheumatologic and immunodeficiency diseases. The immunomodulatory effects can be life-saving, however recent administration can complicate diagnostics when patients later present with symptoms necessitating serologic testing. We evaluated the serologic profile of IVIG for commonly ordered infectious diseases serologies. Methods: Patients were enrolled if they received and were naïve to IVIG therapy. Blood was drawn prior to IVIG and 72–96 hours post-infusion. All samples were tested for: Bartonella, Coccidioides, Brucella, Histoplasma, Coxiella, West Nile, St. Louis, California, Eastern, and Western Encephalitis, Lyme, Dengue, HSV 1 and 2, Chikungunya, cytomegalovirus, varicella zoster, Epstein-Barr and Toxoplasma by standard methodologies (ARUP, Salt Lake City, UT). Pre- and post-infusion antibody concentrations were evaluated to determine the potential false-positive rate of serologic testing. Results: Seven patients received IVIG (renal transplant rejection, two patients; Guillain–Barre syndrome, three patients; bone marrow transplant, two patients). Six of seven patients receiving IVIG had at least one evaluated serology become positive 72 hours after IVIG infusion. Antibodies for CMV, HSV-2, and EBV early antigen D turned positive in three patients. Antibodies for WNV, Coccidioides IgG, and Histoplasma yeast IgG became positive in two patients.Finally, antibodies for HSV-1 and -2, and EBV nuclear antigen each turned positive in one patient. Patients received between 20 and 112.5 g. Of the three patients who received more than 100 g of IVIG, two had at least four serologies turn positive. Of the patients who received <100 g (20–50 g), none had >3 turn positive ( P < 0.05). One patient had three serologies turn negative ( Coccidioides, HSV 2, and EBV Early D) after infusion of 36.5 g of IVIG, with none turning positive. Conclusion: Use of IVIG has increased significantly over the past decade; however, the potential pitfalls in serologic diagnostics associated with receipt of IVIG have not been studied systematically and is likely a confounder in serologic diagnostics causing both false-positive and false-negative results. We found a number of screening and diagnostic serologies can be artificially altered after infusion of IVIG. Disclosures: All authors: No reported disclosures.